PWE-355 Ct-colonography use in incomplete colonoscopy and frail patients. (22nd June 2015) - Pisano, U; Eason, D; Semple, E; Banerjee, A; Docherty, J; Lim, M; Watson, AJ
Abstract : Introduction: CT-colonography (CTC) is a valid alternative to standard colonoscopy in colorectal cancer (CRC). In the context of screening, it is employed only in unsuitable colonoscopy candidates or when colonoscopy is incomplete. With rising numbers in both categories, the use of CTC within our NHS Board has increased over 300% in the last 5 years. Method: 198 consecutive patients who underwent CTC between January 2013–October 2013 were retrieved from a prospectively collected radiology database. Patient who had a CTC were allocated into one of two groups; (1) patients who were "frail, " with cardiovascular, pulmonary, renal impairment or generalised poor mobility or (2) they had an "incomplete" colonoscopy. We analysed the characteristics of the two groups, colonic findings and follow-up rates. Statistical analysis of categorical variables was performed using Chi-square. Differences in mean were sought with the t-test. A p-value <0.05 was considered significant. Results: 116 patients were allocated in the "incomplete" group (M/F: 49/67) and 82 in the "frail" group (M/F: 42/40) (p = 0.27). Mean age was 71 (SD±10) for the "incomplete" group and 72 (SD±12) in the "frail" group (p = 0.51). Isolated and multiple polyps were found in 22 "incomplete" colonoscopy and 14 "frail" patients (11.2% and 7.1%)(p = 0.91): The polyp size was recorded as: 13 cases (6.6%) were <5mm (diminutive), 20 cases (10.1%) between 6–9mm (small) and 13 cases were ≥ 10mm (large). There was no association between polyp size and patient group (p = 0.6, 1.0 and 0.7) and no age difference for polyp sizes (p = 0.89, 0.45, 0.36). 20 colonoscopies (10.1% of total) were subsequently performed after the CTC in the "failed" group and 17 (8.6%) in the "frail" group, with no difference between the groups (p = 0.66). Conclusion: There are no significant difference in lesion and polyp yield between those who "failed" to complete optical colonoscopy and those deemed too "frail" to undergo the endoscopic investigation. The increasing trend for referral for CTC reflects the wider requirement to investigate the elderly and frail population by an established and refined technique. We have increased the use of CTC in our Board, due to a continued decease in use of barium enemas, the need to rule out cancer in patients who are too frail to undergo surgery and an increased confidence in the technique by referrers, after evidence of the equivalence of CTC with colonoscopy. Whilst optical colonoscopy numbers are still climbing significantly as a result of bowel screening, a similar trend for CTC-based screening might be observed in the next years. In our groups of patients, there was no difference in the colonoscopy rate after CTC. Disclosure of interest: None Declared.